Investigating the relationship between changes in oil prices and unemployment rate in Nigeria: Linear and nonlinear autoregressive distributed lag approaches - Isiaka Akande Raifu; Alarudeen Aminu; Abiodun Oluwole Folawewo (Future Business Journal, 2020)
The increasing unemployment in Nigeria has motivated several empirical studies on the causes of the problem in the country. However, attention has not been paid to the contribution of the changes in oil prices to the unemployment problem. As a net exporting oil country, a fluctuation in oil prices in the international market can have impact on economic growth and employment. In the light of this, we investigate the effect of changes in oil prices on unemployment rate in Nigeria, using real oil prices of Brent and West Texas International with linear and nonlinear autoregressive distributed lag (NARDL) estimation methods. Findings from linear ARDL show that changes in oil prices have little or no significant effects on unemployment rate. The NARDL results indicate that an increase and a decrease in oil prices have an insignificant positive effect on unemployment in the short run. However, in the long run, an increase in oil prices worsens unemployment situation, while a decrease has insignificant reducing effect. We also find evidence of a long-run asymmetric relationship between oil prices and unemployment. The need for government to invest oil revenues in generating more electricity or in providing alternative sources of energy with the objective to reduce the costs of production of firms is recommended.
Keywords: E24; L70; C20; 650; Crude oil price; Unemployment rate; ARDL; NARDL